Pengelolaan Program Rencana Strategis Pembangunan Kampung Di Disrik Aifat Utara Kabupaten Maybrat - Turot, Yosephus; Kaunang, Markus; Londa, Very y (JURNAL ILMIAH SOCIETY, 2015)
Implementation of Developments Strategic Plan through the village in the district of North Aifat Maybrat - West Papua has not been effective when linked to the aims of the RESPEK program itself that is the creation of an independent village prosperous society. RESPEK implementation will work well if starting from the planning, implementation and supervision of running well. The method used in this research was qualitative. Data obtained by using three ways: interviews, observation and documentation. The informants determined by purposive in total amounting to 23 peoples. Data were analyzed descriptively. From these results of this research it can be concluded that the ineffective management of RESPEK in the district of North Aifat Maybrat caused by (1) the ineffective planning, notimplementeddeliberationsvillage by the Village Council Head to plan what needs to be built, there was no public participation in the formulation of things what will be built using funds of Respect, the reason people do not participate because there is no consensus that done by the village government. (2) The implementation of development which uses a source of funds of RESPEK misses the point and not in accordance with the operating instructions of activities. Education, women's credit (SPP) and the infrastructure was not running optimally. (3) Supervision, no oversight of the government's RESPEK program management, while people also keep an eye on but no socialization of the government about how the flow monitoring and reporting on violations found, so that peoples often fight with TPKK. Keywords: Management, Strategic Planning, Development